Does induction of labour before the expected date of delivery affect perinatal outcomes? A descriptive study - Shrestha, Prashant; Suwal, Salina (Journal of Patan Academy of Health Sciences, 2025)
Introduction: Induction of labor (IOL) is a common obstetric procedure aimed at achieving vaginal delivery. Traditionally Induction is reserved for low-risk pregnancies at 41 weeks but as there is increasing complications associated with increasing gestational age; emerging evidence suggests benefits of earlier induction at around 39 weeks. This prospective study evaluates whether IOL at different term gestational age would affect perinatal outcome that would help to optimize timing of induction. Method: Conducted at Patan Academy of Health Sciences, 279 obstetric patients were induced after 38 weeks gestation over a three-month period. Patients with medical complications requiring distinct protocols were excluded. Induction and labor monitoring was performed as per hospital protocol. Outcomes assessed were mode of delivery, indications of Cesarean section, presence of meconium-stained liquor and Neonatal admission. Result: Among 279 induced women, 52.68% achieved vaginal delivery, remaining had cesarean section (CS) which was higher in primigravida. CS rate decreased significantly with advancing gestational age from 56.06% at 38–39 weeks to 15.90% at >40 weeks. The failed induction was more common at 38-39 weeks of gestation (28.78%) whereas MSL was more frequent among >39 weeks group (16.67%) requiring emergency CS. Neonatal admissions to nursery were higher in 39–40 weeks group but NICU admissions were seen only among >40 weeks group. There was no neonatal death or intrapartum stillbirth among induced patient however two inductions were done for antenatal IUFD that occurred after 40 weeks of gestation who had no known risk factors. Conclusion: Induction at 39–40 weeks achieves a favorable balance by reducing cesarean section rate and maintaining optimal neonatal outcome. These findings support tailored timing of labor induction to optimize perinatal outcomes.